Tissue eosinophils as a histopathological marker in oral premalignant and malignant lesions: a histochemical study - Shirin Saravani; Hamideh Kadeh; Asma Abil najafzade (Babol University of Medical Sciences, 2017)
Introduction: Although recent studies show the association of eosinophils with different tumors including oral malignancies, the role of eosinophils in premalignant conditions of the oral cavity is not known precisely. Therefore, this study aimed to determine the number of eosinophils in premalignant and malignant conditions of the oral cavity and its role in progression to malignancy. Materials &Methods: This cross-sectional study was done on 50 samples with oral squamous cell carcinoma (OSCC), 18 with verrucous carcinoma, 13 with erosive lichen planus, and 10 with leukoplakia with mild dysplasia after confirmation of histopathological diagnosis. The samples were stained with Sirius Red. The total numbers of eosinophils in 10 areas were counted at a magnification of 400x (eosinophil/10HPF). Data are analyzed with Kruskal-Wallis test, Mann-Whitney test, and Spearman’s correlation test. Results: The mean number of eosinophils in OSCC, verrucous carcinoma, erosive lichen planus, and leukoplakia with mild dysplasia was 90.26, 59.72, 11.08 and 0.0 eosinophil/10HPF respectively. The mean number of eosinophils was significantly higher in malignant (OSCC and verrucous carcinoma) than premalignant (erosive lichen planus and leukoplakia with mild dysplasia) lesions of the oral cavity (P=0.0001). No significant correlation was found between the number of eosinophils with histopathologic grade, gender, and age in OSCC samples.  Conclusion: The greater number of eosinophils is seen in malignant than premalignant lesions of the oral cavity. It is recommended to consider the high number of eosinophils in premalignant lesions as an indicator for a more potential of preliminary oral lesions to undergo malignant transformation.